Impact of Enterprise Resource Planning (ERP) on the Quality of Work of Company Employees: A Brief Review - Fauzi, Teddy Hikmat; Adnani, Latifah; Jamaludin, Maun (LifeSciFi, 2022)
Enterprise resource planning (ERP) is a very complex and high-cost information system that places tremendous demands on a company’s time and resources. Many ERP implementations have been classified as failures because the company did not achieve its stated goals. This article identifies the success factors, software selection steps, and implementation procedures important for successful implementation in manufacturing companies. Implementing Enterprise Resources Planning (ERP) in the company is part of the company’s internal business strengthening strategy to increase strong competitiveness and manage the company professionally, efficiently, and effectively, as well as apply the principles of transparency, accountability, responsibility, independence, and fairness. ERP implementation in Indonesia has more impact tactical than strategic. The main objectives of our work are to review and analyses key articles on the impact of ERP projects on work quality and quantity. The results obtained are that the implementation of ERP has a positive effect on employee performance, and the implementation of the ERP system has a positive impact because the informants produce more work in one period.